Micro and Rural Finance in Ghana : Evolving Industry and Approaches to Regulation - Steel, William F.; Andah, David O. (World Bank, Washington, DC, 2012)
The note reviews the structure and performance of Ghana's rural, and micro-finance institutions (RMFIs), through a financial system, namely comprising three main categories: formal, semi-formal, and informal systems. It then analyzes the liberalization of its financial policies (late 1980s) and the supervision regime, indicating that while Ghana's approach has yielded a wide range of RMFIs, and products - potentially outreaching the poor based on savings mobilization - it has also permitted the easy entry of institutions with weak management, and internal controls. This demonstrates the difficulty in striking the right balance between encouraging entry and innovation, and establishing adequate supervision capacity.